Determination and Notification of Quality Index of Fruits Using Non-Destructive Methods - Soundarya S, Syed Wasim Nihal, Vaishnavi R, V Tejaswini , Prabhat Kumar Panda (International Journal of Advanced Science and Technology, 2020)
Nowadays fruits are getting wasted due to non-consumption at proper time. To prevent this, destructive and non-destructive methods can be used. Destructive methods that involve cutting the fruit, piercing the fruit or using chemicals are commonly used. These methods harm the fruit and can make them inedible. Hence, non-destructive method has been proposed to overcome the drawback mentioned above. The main objective of this paper is to determine the quality index of fruits using non-destructive methods and notify the same to the user. Yolo, ImageAI, OpenCV, Keras and TensorFlow along with Python have been adopted to determine the quality index of fruits. The control system has been implemented using Arduino and IoT is implemented using NodeMCU to notify the user. This project has been successfully implemented and tested for varieties of Apples. Quality index of apple has been determined and notified with an increased accuracy